Teachers perceptions about discipline in efl classroom - Sanchez Ushca, Derlis David (2023)
Classroom management for control indiscipline is essential for an effective class, teachers always have to find how to manage these cases and their performance. Set rules or class layout are simple strategies that help teachers to manage a class. Without classroom strategies, teachers would not be able to assure an effective learning environment for language users. Those problems could generate indiscipline inside the classroom, and that huge problem can affect teachers' performance in a long way. Due to this, the present study used qualitative research with the aim to determine teachers’ perception about discipline management in EFL classes in ‘Nuestra Señora de Pompeya’ Educational Unit. Data analysis was done by the phenomenological method, in which the purpose was to analyze teachers’ experiences, perceptions, classroom strategies, and procedures. To get this information, a semi-structured interview was applied following the non-random selection based on convening sampling. Out of even teachers of Foreign Language Areas, just three who follow the criteria defined by the researcher were selected. Those three selected teachers had experience with different grades of education and have different roles in Foreign Language Areas. In addition, observational journals were implemented to take notes about students’ behavior. This study shows teachers’ point of view about the importance of classroom management to control indiscipline in class and the way that they perceive their own performance after a difficult class. By journal, and interview, teachers presented negative aspects that were a consequence of the indiscipline problems, which affected their performance. Feelings like disappointment, frustration and getting lost in class were the most common aspects that teachers mentioned they had experienced, and those emotions could affect classroom efficiency. Also, indiscipline affects students’ and teachers’ performance and motivation. It generates that efficiency of class diminishes if teachers do not apply classroom management strategies.